Clustering of Customers Based on Shopping Behavior and Employing Genetic Algorithms - Bafghi, E. P. (Engineering, Technology & Applied Science Research, 2017)
Clustering of customers is a vital case in marketing and customer relationship management. In traditional marketing, a market seller is categorized based on general characteristics like clients’ statistical information and their lifestyle features. However, this method seems unable to cope with today’s challenges. In this paper, we present a method for the classification of customers based on variables such as shopping cases and financial information related to the customers’ interactions. One measure of similarity was defined as clustering and clustering quality function was further defined. Genetic algorithms been used to ensure the accuracy of clustering.